2016
DOI: 10.1097/dss.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled, Double-Blind, Half-Head Study to Assess the Efficacy of Platelet-Rich Plasma on the Treatment of Androgenetic Alopecia

Abstract: Application of PRP showed a positive effect on AGA and could be regarded as an adjuvant therapy for AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
209
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(220 citation statements)
references
References 35 publications
5
209
0
6
Order By: Relevance
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…PRP is a biological product defined as a portion of the plasma fraction of autologous blood with a platelet concentration above the baseline (before centrifugation) [22]. As such, PRP contains not only a high level of platelets but also the full complement of clotting factors, the latter typically remaining at their normal, physiologic levels [23].…”
Section: Definitionmentioning
confidence: 99%
“…The currently available treatments for AGA are sometimes perceived as having limited effectiveness; therefore, the identification of new therapies for this pathology is of utmost importance [102,103]. New possible offline treatments for AGA, such as topical finasteride, injectable dutasteride, laser therapy and PRP, have recently emerged and have been claimed to have hair growth-promoting or anti-hair loss effects.…”
Section: Emerging Treatmentsmentioning
confidence: 99%